(untitled) (Journal of Geography and Environmental Management, 2019)
Contained a general hydrological and hydrogeological characteristics and the results of hydrogeological forecast of the rate of sinking career Shaimerden lead-zinc deposit in Shaimerden Kostanai region and technical solutions for the first phase of land reclamation. Based on the analysis of the chemical composition of the natural lakes in the research area of the field and observing the change in salinity of the lake water drainage receiver lake Koyandykopa carried out is assess changes in salinity of its waters after the cessation of pumping, showing an increase in mineralization with increasing evaporation from the surface. Forecast assessment of mineralization and chemical composition of the newly formed lake on the site of a career built on the basis of its share in the groundwater inflow of water of different aquifers and their chemical composition. The water quality limits its use only as conservation nature. The results of evaluation of the environmental impact of remediation, providing temporary negative (dust) and positive (recovery of the aesthetic appearance of damaged land) effects.